Monitoring Insulin and Glucose Levels in Hospital Najaf: A Critical Analysis of Diabetes Management - Ahmed Omar Kafi; Suha Salah Khalaf; Areej Amer Kafi; Ahmed Samer Khalaf; Hawraa Hammoud Hussein Jaber; Nagham Ahmed Saleh (Zien Journals, 2023)
Diabetes mellitus, characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both, is a global health concern with increasing prevalence. In the city of Najaf, Iraq, Hospital Najaf plays a pivotal role in managing diabetes cases for a substantial population. Effective diabetes management is critical, as uncontrolled diabetes can lead to a range of complications. Monitoring insulin and glucose levels is pivotal in this context. This study employs a mixed-methods approach to comprehensively assess diabetes management at Hospital Najaf, encompassing both qualitative and quantitative data sources. Qualitative data was gathered through interviews with healthcare professionals and patients, while quantitative data included the analysis of medical records and surveys. Statistical analysis was performed using SPSS. Results reveal significant differences in sugar and insulin levels between healthcare professionals and patients with diabetes, underlining the importance of monitoring and intervention. Patient interviews highlight the need for education and culturally sensitive care. This study's insights aim to contribute to enhanced diabetes management and the well-being of individuals with diabetes in Najaf and beyond.
Keywords: contribute; professionals; individuals; sensitive